Kebijakan 13th Five Year Plan Tiongkok Sebagai Implementasi Paris Agreement Tahun 2016-2020 - Baldata Agnia Majid (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Climate change and global warming are environmental phenomena with large negative impacts for various countries in the international world. This presents the Paris Agreement as a commitment for ratifying countries to address global warming by reducing carbon gas emissions based on the NDC (National Determined Contribution). One of the countries that ratified the Paris Agreement is China. This is motivated by the large number of industrial sectors in China that use coal as the main energy source in driving their industry, so this has also caused China to become one of the countries with the largest carbon emission emitters in the world and has an impact on the domestik environment such as bad air pollution. and natural disasters. This study will discuss China's efforts as a country that ratified the Paris Agreement in reducing carbon gas emissions and demonstrate its commitment by implementing environmentally friendly strategies and implementations in the 13th Five Year Plan policy. Furthermore, this study will also analyze China's commitment to using Hugh Dyer's green theory and the three concepts from Tayyar's green theory. This research uses a qualitative descriptive approach with sources obtained from literature studies. The findings in this study are that China has demonstrated its commitment to addressing climate change by reducing carbon gas emissions in line with the goals of the Paris Agreement, namely by pursuing various strategies contained in the 13th Five Year Plan policy for reducing carbon gas emissions in the domestik sphere. This can be seen from the existence of values and goals in pro-environmental policies by implementing the